Balancing Agility and Formalism in Software Engineering - Meyer, Bertrand (Springer, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the Second IFIP TC 2 Central and East Conference on Software Engineering Techniques, CEE-SET 2007, held in Poznan, Poland, in October 2007.